Wireless power strip socket - Johari Halim Shah, Nadira; Mohammad, Muhamad Amiru Amin; Hamzah, Muhammad Afiq Fikri; Mohd Hilmee, Muhammad Mustaqim (Penerbit UTHM, 2020)
Today, the demand on the electricity consumption is increasing throughout the society. Unfortunately, it goes without saying that in spite of the heavy consumption of the electricity, the number of damages and fatal accidents also caused by electricity if consumers neglected the safety precaution related to it. In fact, based on the statistics of the electrical accident released by the Energy Commission (ST), 13 cases of electric accidents occurred nationwide with seven involving the deceased in 2015 [1]. Researchers have taken the opportunities to invent many kinds of products or mechanism to minimize the losses created by the malfunctioning of the electrical devices. Having thought of the situation, a portable device using smartphones has been designed to encounter this matter.